Galactic nonlinear dynamic model - De Melo, C. A.M. [UNESP]; Resende, S. T. (World Scientific Publishing, 2009)
We develop a model for spiral galaxies based on a nonlinear realization of the Newtonian dynamics starting from the momentum and mass conservations in the phase space. The radial solution exhibits a rotation curve in qualitative accordance with the observational data. © 2009 World Scientific Publishing Company.
Keywords: Dark matter; Galactic rotation curves; Mathematical modeling